Lectotypification of Cryptocarya anamalayana Gamble (Lauraceae) with a note on its fruits - Bachan, K.H. Amitha; Robi, A.J.; Pradeep, A.K.; Udayan, P.S. (Bangladesh Journal of Plant Taxonomy, 2018)
Not available. Bangladesh J. Plant Taxon. 25(1): 107-111, 2018 (June)